Registration of 'CP 14‐1934' sugarcane for Florida organic soils. Issue 1 (13th December 2022) - Coto Arbelo, Orlando; Davidson, Wayne; Islam, Md S.; Sandhu, Hardev S.; Zhao, Duli; Sood, Sushma; Momotaz, Aliya; Baltazar, Miguel; Gordon, Vanessa S.
Abstract: 'CP 14‐1934' (Reg. no. CV‐210, PI 700310) sugarcane cultivar, a complex hybrid of Saccharum spp., was developed through cooperative research of the USDA‐ARS, the University of Florida, and the Florida Sugarcane League. The Florida Sugarcane Variety Committee released CP 14‐1934 in June 2021 for commercial cultivation on organic (muck) soil. CP 14‐1934 originates from a cross CPX11‐1041 between CP 07‐2460 (female parent) and CP 06‐2335 (male parent). CP 14‐1934 was released due to its high cane yield; high sucrose yields; acceptable commercial recoverable sucrose; and resistance to brown rust (tested positive to Bru 1 marker), orange rust, sugarcane mosaic virus strain E (mosaic), and ratoon stunting disease. CP 14‐1934 was found moderately resistant to leaf scald and to have intermediate freeze tolerance. Based on results of three harvests cycles over five locations in final‐stage replicated yield trials (Stage 4) on muck soils, CP 14‐1934 cane and sucrose yields were 17.8 and 19.8% greater than the mean of reference cultivars, respectively. CP 14‐1934 rarely flowers in Florida's climate. The new released cultivar CP 14‐1934 is expected to increase the profitability and the efficiency in the use of resources of Florida sugarcane growers. Core Ideas: 'CP 14‐1934' sugarcane was released for cultivation in organic (muck) soil in Florida. 'CP 14‐1934' was released because of its high yield potential compared with commercial reference cultivars. 'CP 14‐1934' is resistant or partially resistant to economical important sugarcane diseases. 'CP 14‐1934' had intermediate tolerance to freeze.